Factors Affecting the Improvement of the Performance of the Rankine cycle Heat Exchanger (Used in Summer and Winter Cycle) Based on Groundwater Energy in Damsarkho - الغدا عُلا; جابر ديبة; دارين برجيه (Latakia University Journal -Engineering Sciences Series, 2024)
Heating and air conditioning devices are major consumers of electrical energy, so renewable energy technology was used to make these devices operate on a renewable and sustainable energy source, such as a heat pump. In Damsarkho, previous studies reported that its groundwater can be used in a heat pump for heating and air conditioning purposes according to specific hydrogeological, geochemical and geothermal conditions. The research focuses on the heat exchanger performance of a closed-circuit (air-groundwater) heat pump, in which the heat exchanger is placed inside the well. The performance of the exchanger is improved by designing it to suit the specific conditions for exploiting groundwater in Damascus, while studying the factors affecting improving its performance in order to increase the pump efficiency and reduce the manufacturing cost. A set of design calculations were performed, including: (mass flow of air and groundwater, Reynolds number, convective heat transfer coefficients for groundwater and Freon, the percentage increase in the total heat transfer coefficient for the exchanger before and after the fin, the percentage increase in the total heat transfer coefficient with different values ​​for each of the conductivity coefficients) Thermocouple of the fins, the height of the exchanger, the distance between the windings and the helix pitch). After obtaining the results, they were presented in tables and represented in graphs using Excel. The results show that the factor with the greatest impact on increasing the overall heat transfer coefficient among the factors studied is the fin width with an increase of 3.9%, followed by the inner tube diameter with an increase of 3.8%. The third factor in terms of priority in influence is the number of turns of the ileal tube with an increase 3.6%, while the two factors, the spiral pitch and the tube height, have an equal effect with an increase of 2.9% for each. The last factor is the thermal conductivity coefficient of the fins when they were copper, with an increase of 2.7%.